Curcumin Stimulates the Antioxidant Mechanisms in Mouse Skin Exposed to Fractionated γ-Irradiation - Ganesh Chandra Jagetia; Golgod Krishnamurthy Rajanikant (MDPI AG, 2015)
Fractionated irradiation is one of the important radiotherapy regimens to treat different types of neoplasia. Despite of the immense therapeutic gains accrued by delivering fractionated irradiation to tumors, the radiation burden on skin increases significantly. Low doses of irradiation to skin adversely affect its molecular and metabolic status. The use of antioxidant/s may help to alleviate the radiation-induced changes in the skin and allow delivering a higher dose of radiation to attain better therapeutic gains. Curcumin is an antioxidant and a free radical scavenging dietary supplement, commonly used as a flavoring agent in curries. Therefore, the effect of 100 mg/kg body weight curcumin was studied on the antioxidant status of mice skin exposed to a total dose of 10, 20 and 40 Gy γ-radiation below the rib cage delivered as a single fraction of 2 Gy per day for 5, 10 or 20 days. Skin biopsies from both the curcumin treated or untreated irradiated groups were collected for the biochemical estimations at various post-irradiation times. The irradiation of animals caused a dose dependent decline in the glutathione concentration, glutathione peroxidase, and superoxide dismutase activities and increased the lipid peroxidation in the irradiated skin. Curcumin treatment before irradiation resulted in a significant rise in the glutathione concentration and activities of both the glutathione peroxidase and superoxide dismutase enzymes in mouse skin, whereas lipid peroxidation declined significantly. The present study indicates that curcumin treatment increased the antioxidant status of mouse exposed to different doses of fractionated γ-radiation.